Analytical Modeling of I-beam as a Sandwich Structure - MAGNUCKI, Krzysztof; LEWIŃSKI, Jerzy (Engineering Transactions, 2018)
The paper is devoted to an analytical model of I-beam, with consideration of the shear effect. The model is based on the sandwich beam theory. The field displacements and strains are formulated with consideration of a nonlinear hypothesis of flat cross-section deformation of the beam. The governing differential equations for the I-beam are obtained based on the principle of stationary total potential energy. The shear effect of the beam is illustrated for the threepoint bending case. The analytical solution is compared to FEM numerical calculation. The results of the analysis are presented in Tables and Figures.